2016
DOI: 10.1007/s40808-016-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impacts of future climate change on plant communities in the Himalaya: a case study from Eastern Himalaya, India

Abstract: That the Himalaya are warming at much higher rates than the global average is known. Here, we assess the future potential distribution of major plant communities in Sikkim Himalaya due to climate change using field observations and maximum entropy modelling approach. We collected data on presence and elevational distribution ranges of 584 endemic angiosperm species during field surveys at 121 sampling locations using 625 study plots and along an elevational gradient of 300-5,300 m. This field data was suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 63 publications
3
49
0
1
Order By: Relevance
“…This finding was consistent with previous studies that have also found a northward shift in the spatial distribution of suitable species climatic habitat [44]. Species would shift their distributions to higher latitudes in response to warming climates, because temperature outside their thermal tolerance would decrease their capacity to survive [44,[71][72][73].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was consistent with previous studies that have also found a northward shift in the spatial distribution of suitable species climatic habitat [44]. Species would shift their distributions to higher latitudes in response to warming climates, because temperature outside their thermal tolerance would decrease their capacity to survive [44,[71][72][73].…”
Section: Discussionsupporting
confidence: 92%
“…To reduce the uncertainty arising from the single general circulation model (GCM), we used data from multiple different GCMs [2, 43,44] including BCC-CSM1-1, CCSM4, GISS-E2-R, IPSL-CM5A-LR, HadGEM2-ES, MIROC-ESM-CHEM, MRI-CGCM3, and NorESM1-M. For each GCM, we downloaded bioclimatic variables for four Representative Concentration Pathways (RCP: 2.6, 4.5, 6.0, and 8.5). We assumed that four topographical variables remain unchanged over the next 70 years.…”
Section: Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Skills in climate model outputs have improved over time, and more recently, a set of climate change scenarios known as representative concentration pathways (RCPs) has been adopted by climate researchers to provide a range of possible futures for the evolution of atmospheric composition and implications on various sectors (Collins et al 2013;Gharbia et al 2016;Zahid and Iqbal 2015;Deb et al 2018;Manish et al 2016;Clarke et al 2007;Smith and Wigley 2006;Thomson et al 2011;Wise et al 2009). However, it needs to be presented in a format which can provide useful information to growers.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change affects species distributions (Parmesan and Yohe 2003), and species with a restricted distribution may be more vulnerable to the changes in climatic factors that determine the boundaries of their distributions (Thuiller et al 2005, Manish et al 2016. Understanding the extent to which a geographical range shift is needed for species to be able to track their climate niche in response to climate change is currently a crucial scientific task.…”
Section: Introductionmentioning
confidence: 99%